Laparoscopic Versus Abdominal Myomectomy Postoperative Outcomes - Nicel Taşdemir; Cem Çelik; Remzi Abalı; Ayşegül Kayalı; Abdulaziz Gül; Özkan Özdamar (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Myomas are benign uterine tumors affecting 25-70% of reproductive-aged women. Myomectomy remains the gold-standard for women who request preservation of fertility. We performed an observational investigation of a series of patients scheduled for laparoscopic or abdominal myomectomy to evaluate post-surgical parameters, operation duration, after laparoscopic and abdominal myomectomy. STUDY DESIGN: The manuscript involved data from women who were operated between February 2011 and February 2013. Patients enrolled into the study were compared according to the age, body weight, height, body mass indexes (BMI), the number of the myomas, and operation time. Additionally, pre and postoperative hemoglobin and hematocrit levels and the length of hospital stay were noted. RESULTS: Twenty-two patients underwent laparoscopy and 15 patients underwent laparotomy. Mean age was 40.1±9.1 in laparoscopy group and 38.5±6.7 in laparotomy group(p=0.513). Mean BMI was 26.1±4.1 in laparoscopy group and 27.9±5 in laparotomy group (p=0.281). Myoma numbers were similar in both groups (p=0.232). Operation duration was longer in laparoscopy group (148.33±66.26) compared to laparotomy group (102.75±42.37) (p=0.013). Preoperative and postoperative hemoglobin and hematocrit levels were similar in both groups (Hemoglobin ppre=0.680, ppost=0.499; Hematocrit ppre=0.946, ppost=0.499). The pre and post-operative hemoglobin and hematocrit levels were comparable (p=0.782 and 0.717). The median value of hospitalization duration for laparoscopy group was 2.5 days(2-8) and for laparotomy group it was 3 days (2-6) (p=0,008). CONCLUSION: Our study demonstrated laparoscopic approach needed significantly longer operative time but shorter hospitalization. We think that the time loss during the morcellation is important in the prolongation of the operation. Not observing any differences in variations of hematologic parameters supports the idea that the time is lost during the morcellation. In selected group of patients, laparoscopic myomectomy is an attractive alternative to laparotomic myomectomy, providing clear advantages such as shorter hospitalization duration.